Lower plasma trans-4-hydroxyproline and methionine sulfoxide levels are associated with insulin dysregulation in horses - Kenéz, Ákos (BMC Vet Res, 2018)
BACKGROUND: Insulin dysregulation in horses is a metabolic condition defined by high insulin concentrations in the blood and peripheral insulin resistance. This hyperinsulinemia is often associated with severe damage in the hooves, resulting in laminitis. However, we currently lack detailed information regarding the potential involvement of particular metabolic pathways in pathophysiological causes and consequences of equine insulin dysregulation. This study aimed to assess the dynamic metabolic responses given to an oral glucose test (OGT) in insulin-sensitive and insulin-dysregulated horses by a targeted metabolomics approach to identify novel metabolites associated with insulin dysregulation. RESULTS: Oral glucose testing triggered alterations in serum insulin (26.28 ± 4.20 vs. 422.84 ± 88.86 μIU/mL, p < 0.001) and plasma glucose concentrations (5.00 ± 0.08 vs. 9.43 ± 0.44 mmol/L, p < 0.001) comparing basal and stimulated conditions after 180 min. Metabolome analyses indicated OGT-induced changes in short-chain acylcarnitines (6.00 ± 0.53 vs. 3.99 ± 0.23 μmol/L, p < 0.001), long-chain acylcarnitines (0.13 ± 0.004 vs. 0.11 ± 0.002 μmol/L, p < 0.001) and amino acids (2.18 ± 0.11 vs. 1.87 ± 0.08 μmol/L, p < 0.05). Kynurenine concentrations increased (2.88 ± 0.18 vs. 3.50 ± 0.19 μmol/L, p < 0.01), whereas spermidine concentrations decreased during OGT (0.09 ± 0.004 vs. 0.08 ± 0.002 μmol/L, p < 0.01), indicating proinflammatory conditions after oral glucose load. Insulin dysregulation was associated with lower concentrations of trans-4-hydroxyproline (4.41 ± 0.29 vs. 6.37 ± 0.71 μmol/L, p < 0.05) and methionine sulfoxide (0.40 ± 0.06 vs. 0.87 ± 0.13 μmol/L, p < 0.01; mean ± SEM in insulin-dysregulated vs. insulin-sensitive basal samples, respectively), two metabolites which are related to antioxidant defense mechanisms. CONCLUSION: Oral glucose application during OGT resulted in profound metabolic and proinflammatory changes in horses. Furthermore, insulin dysregulation was predicted in basal samples (without OGT) by pathways associated with trans-4-hydroxyproline and methionine sulfoxide, suggesting that oxidative stress and oxidant–antioxidant disequilibrium are contributing factors to insulin dysregulation. The present findings provide new hypotheses for future research to better understand the underlying pathophysiology of insulin dysregulation in horses. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12917-018-1479-z) contains supplementary material, which is available to authorized users.